2020
DOI: 10.3390/en13164216
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Design of Combined Two-Tank Latent and Metal Hydrides-Based Thermochemical Heat Storage Systems for High-Temperature Waste Heat Recovery

Abstract: The integration of thermal energy storage systems (TES) in waste-heat recovery applications shows great potential for energy efficiency improvement. In this study, a 2D mathematical model is formulated to analyze the performance of a two-tank thermochemical heat storage system using metal hydrides pair (Mg2Ni/LaNi5), for high-temperature waste heat recovery. Moreover, the system integrates a phase change material (PCM) to store and restore the heat of reaction of LaNi5. The effects of key properties of the PCM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…This model was already validated in our previous works [9,16,41]; therefore, the reader is referred to these works for model validation to avoid data redundancy.…”
Section: Numerical Settings and Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…This model was already validated in our previous works [9,16,41]; therefore, the reader is referred to these works for model validation to avoid data redundancy.…”
Section: Numerical Settings and Validationmentioning
confidence: 99%
“…The rate of melting fraction is generally defined as a symmetric Gaussian distribution centered in T m . As a result, the melting fraction is a smoothed Heaviside function [41]:…”
mentioning
confidence: 99%
“…Additionally, Nyamsi, S.N. et al [16] demonstrated the significant potential harbored by the incorporation of thermal energy storage systems (TES) in waste heat recovery applications, greatly enhancing energy efficiency. This study presented a two-dimensional mathematical model to analyze the efficiency of a two-tank thermochemical heat storage system utilizing Mg 2 Ni/LaNi 5 metal hydrides for high-temperature waste heat recovery.…”
Section: Introduction 1research Backgroundmentioning
confidence: 99%
“…A model for material selection in the design process described in [2] uses group-generalized Pythagorean fuzzy weighted average (GGPFWA) operator to aggregate the value of each material. The technique proposed in [3] integrates different multi-criteria decision-making (MCDM) approaches for selection of the most appropriate material for bio-oil conversion during pyrolysis, while the multi-objective optimization of the performance indexes is used for selection of phase change material (PCMs) for combined thermochemical-latent heat storage systems in [4]. The proposed methodology with decision-making algorithm in [5] which includes a developed internet-of-things (IoT) interface and the analytical hierarchy process (AHP) is applied in the field of an electrical power distribution system.…”
Section: Introductionmentioning
confidence: 99%